Prueba de rendimiento en cinco accesiones de avena (Avena sativa L.), con la utilización de dos dosis de plata coloidal, en las etapas de desarrollo vegetativo y pre floración, en Laguacoto III, cantón Guaranda, provincia Bolívar - Toaquiza Pallo, Celia Verónica (2023)
Oats are a cold climate grass rich in carbohydrates, supports grazing better, are more precocious, withstand moisture, soil acidity, salinity, control erosion better, and do not cause meteorism or pasturing in animals. In Ecuador, the Instituto Nacional de Investigaciones Agropecuarias - INIAP (National Institute of Agricultural Research) has been able to launch new varieties to the market and validate promising lines with resilient characteristics. This research was carried out in the agroecological zone of Laguacoto III, Guaranda canton, Bolivar province. The objectives were: i) Characterize the agronomic and productive development of oat accessions. ii) Determine the effect of the doses of colloidal silver on vegetative development and yield of oats. iii) Determine the treatment with which greater development and production is obtained. iv) Establish the economic efficiency of oat cultivation through the benefit-cost ratio of the different treatments. A Randomized Complete Block Design (RCBD) was applied, with three replications. Five oat accessions were evaluated in two doses of colloidal silver and a control. For yield and agronomic traits, analysis of variance, Tukey's test at 5% for comparison of averages, correlation analysis and simple and multiple regression at 5% were performed. According to the results, the highest average yield was T11: AS-11-005 + 1 cc/L with 5290.1 kg/ha and T10: AS-11-005 + 1.25 cc/L with 5203.5 kg/ha. In the plant vigor (PV) of the treatments under study, on average 20.00% presented very good plant vigor (scale 2), while 80.00% of the treatments presented excellent vigor, while in the growth habit of the evaluated treatments 100% presented erect type. Economically, the technological alternative with the highest net benefit based solely on the costs that varied by treatments was T11: AS-11-005 + 1.25 cc/L; in relation to Benefit Cost B/C, the producer of this grass has a profit of $1.56 USD for each dollar invested.